Evolutionary origin and status of two insect acetylcholinesterases and their structural conservation and differentiation. Issue 1 (January 2015) - Cha, Deok Jea; Lee, Si Hyeock
SUMMARY Acetylcholinesterase (AChE) plays a pivotal role in synaptic transmission in the cholinergic nervous system of most animals, including insects. Insects possess duplicated AChE gene loci (ace1 vs. ace2) encoding two distinct AChEs (AChE1 and AChE2). A phylogenetic analysis suggested that the last common ancestor of two aces shared its origin with Platyhelminthes. In addition, the ace duplication event likely occurred after the divergence of Protostomian but before the split of Ecdysozoa. The ace1 lineage exhibited a significantly lower evolutionary rate (d and dN/dS ratio) than the ace2 lineage, suggesting that the ace1 lineage has retained the essential function of synaptic transmission following its duplication. Therefore, the putative functional transition from ace1 to ace2 observed in some Hymenopteran insects appears to be a local and relatively recent event. The amino acid sequence comparison and three‐dimensional modeling of insect AChEs identified a few consistent differences in the amino acid residues in functionally crucial domains between two AChEs, which are likely responsible for the functional differentiation between two AChEs. A unique amino acid substitution causing a dramatic reduction in the catalytic activity of AChE1 in some Hymenopteran insects was suggested to be responsible for the aforementioned functional transition of ace.